PENTINGNYA ETIKA DAN KOMUNIKASI BAGI PUBLIC RELATION - Nasichul Anwar (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Ethics and communication play an important role in the practice of Public Relations (PR), thus influencing the way organizations interact with the public and stakeholders. This article discusses the close relationship between ethics, PR responsibilities, and effective communication in the context of PR, using a descriptive qualitative approach with a literature study method, this article analyzes various sources such as book literature, journals, and online references. The results show that ethics form the moral foundation for PR, while effective communication enables the implementation of ethical values in daily practice. The responsibilities of a PR include the need for integrity, communication quality, and social responsibility in maintaining a positive image of the organization. So the success of PR depends on the balance between ethics and adequate communication, creating an environment conducive to a positive relationship between the organization and its public.